What can we learn from treatments of oral lichen planus? - Wu, Tingting; Bai, Yang; Jing, Yin; Chen, Fangchun (Frontiers in Cellular and Infection Microbiology, 2024)
Oral lichen planus (OLP), a T-lymphocyte-mediated disease of the oral mucosa, has a complex pathogenesis that involves a number of factors. The disease is characterized by recurrent episodes and requires continuous follow up, and there is no curative treatment available. Erosive lichen planus, among others, has a risk of malignant transformation and requires standardized treatment to control its progression. Different clinical subtypes of oral lichen planus require appropriate treatment. Pharmacological treatments are the most widely available and have the greatest variety of options and a number of novel pharmacological treatments are presented as highlights, including JAK enzyme inhibitors. The second is photodynamic therapy, which is the leading physiological treatment. In addition, periodontal treatment and psychological treatment should not be neglected. In this review, we briefly discuss the most recent developments in therapies for oral lichen planus after summarizing the most widely used clinical treatments, aiming to provide different proposals for future clinical treatment.